2002
DOI: 10.1002/eat.10071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among body image, exercise behavior, and exercise dependence symptoms

Abstract: It was concluded that after controlling for the effects of BMI and exercise behavior, primary exercise dependence symptoms were not strong predictors on body image, especially for females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(111 citation statements)
references
References 14 publications
8
95
1
7
Order By: Relevance
“…Davis and Fox (1993) reported that excessive exercise was associated with greater body satisfaction, whilst others reported negative associations. Hausenblas and Fallon (2002) found that exercise addiction was not a strong predictor of body dissatisfaction, particularly in women.…”
Section: Exercise Addictionmentioning
confidence: 86%
“…Davis and Fox (1993) reported that excessive exercise was associated with greater body satisfaction, whilst others reported negative associations. Hausenblas and Fallon (2002) found that exercise addiction was not a strong predictor of body dissatisfaction, particularly in women.…”
Section: Exercise Addictionmentioning
confidence: 86%
“…Greater exercise has been shown to predict higher body satisfaction and lower SPA for males, whereas BMI seems to be a stronger predictor of SPA for females (Hausenblas & Fallon, 2002). However, the direction of the SPAexercise relationship remain unclear as SPA has been identified both (i) as a potential barrier to exercise, due to concerns of showing one's physique to others in an exercise setting, and (ii) as an incentive or motive to exercise in order to reduce SPA via the development of a fitter and more attractive physique (see Martin Ginis & Leary, 2004).…”
Section: Exercise and Social Physique Anxietymentioning
confidence: 99%
“…In particular, individuals are more likely to participate in slimming programs due to current societal preferences for slimmer role models. In fact, they sometimes exercise solely for these reasons (24). It is expected that individuals who have better physical performance and who perform physical exercises would have lower SPC than those who do not practice physical exercises.…”
Section: Introductionmentioning
confidence: 99%